Validation of Integrated Periphyton Technology in Mixed Sex Culture of Giant Freshwater Prawn, Macrobrachium Rosenbergii: Insights into Impact of Heterogenous Independent Differentiation and Gender on Growth Dynamics in Grow Out - David Marioni,; Nor Azman Kasan,; Liew Hon Jung,; Victor Torres Rosas,; Ponnumony Vethamony,; Jassim Abdulla Al-Khayat,; Mhd Ikhwanuddin, (Tropical Life Sciences Research, 2025)
This study evaluated the performance of mixed sex postlarval (PL) populations of giant freshwater prawn, Macrobrachium rosenbergii, cultured under Integrated Periphyton Technology (IPT) and Recirculating Aquaculture System (RAS) conditions. The trials were conducted in triplicate over 44 days of nursery culture (T1), followed by 60 days of growth after size separation (T2 and T3). The carbon-to-nitrogen (C:N) ratios were optimised through molasses supplementation. The water quality parameters in both systems remained within acceptable ranges. Key performance indicators, including body weight, survival rate, average daily gain, specific growth rate, harvest biomass and feed conversion ratio (FCR), were analysed across T1 and T2. While nursery performance (T1) was not significantly different between the IPT and RAS systems, Morphologicaldistinctions among male morphotypes (BC, OC and SM) and females were characterised, with sex specific growth performance compared across T1 and T2, as were sizeseparated populations in T3. IPT demonstrated more effective production of Blue Claw (BC) prawns during the grow-out phase (T2). IPT, a zero-discharge system, matched or outperformed RAS, while eliminating the need for external effluent management, while equivalent FCR did not establish periphyton as a supplemental food source within the production volume. Although size separation yielded variable benefits, enhancement of overall productivity was inconclusive. This study highlights IPT as a sustainable alternative to conventional RAS, offering equivalent FCR, and lower energy consumption, and land resource requirement. Further investigations are warranted to optimise intensive IPT systems for economic feasibility and environmental sustainability, contributing to broader advancements in aquaculture.